One-off events in the market comparison method - Janas, Krzysztof (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
The aim of the article One-off events in the market comparison method is to focus on one-off events occurring in public companies on the basis of which ratios are calculated to estimate companies’ value by the market comparison method. The author of the publication tries also to answer how these events should be taken into account in the calculation of market multiples. In the first part of the paper, single economic events are defined, the occurrence of which causes significant changes in the underlying indicators. With the aid of examples from the Polish capital market it is shown what influences the final result of the estimation of the value of a company. Based on a critical review of practical approaches to consider the one-off events in the comparative method and based on the simulation of the variability of the final result of the valuation depending on the adopted approach, the author presents a solution to the problem approached in the article. The presented work is an especially important topic from a practical point of view. It complements the company valuation theories in the field of application of the method of market comparisons for estimating the value of the company